Answer:
[tex]g(x) = 2^{x-3}[/tex] is the correct function equation that shows the corresponding transformation as shown in figure.
Step-by-step explanation:
Let us consider the function f(x) = bˣ. Lets add a constant c to the input of parent function i.e f(x) = bˣ. It would produce a horizontal translation move by c units, along x axis .
If c > 0, there will be translation to the "left" by "c" units.
If c < 0, there will be translation to the "right" by "c" units.
So, by analyzing the coordinate locations of the function f(x) = 2ˣ and g(x), it is clear that [tex]g(x) = 2^{x-3}[/tex] is the correct function equation that shows the corresponding transformation. Because the g(x) also does has a translation to the 'right'.
It can be further verified as:
Lets check the coordinate locations of f(x) = 2ˣ and [tex]g(x) = 2^{x-3}[/tex] at the the points y = 1, y = 2 and y = 4
At y = 1, the function f(x) = 2ˣ has the location at (0, 1) as 2ˣ = 2° ⇒ x = 0.
At y = 1, the function [tex]g(x) = 2^{x-3}[/tex] has the location at (3, 1) as [tex]2^{0} = 2^{x-3}[/tex] ⇒ x-3 = 0 ⇒ x = 3. It has a translation to the "right".
At y = 2, the function f(x) = 2ˣ has the location at (1, 2) as 2ˣ = 2¹ ⇒ x = 1.
At y = 2, the function [tex]g(x) = 2^{x-3}[/tex] has the location at (4, 2) as [tex]2^{1} = 2^{x-3}[/tex] ⇒ x-3 = 1 ⇒ x = 4. It has a translation to the "right".
At y = 4, the function f(x) = 2ˣ has the location at (2, 4) as 2ˣ = 2² ⇒ x = 2.
At y = 4, the function [tex]g(x) = 2^{x-3}[/tex] has the location at (5, 4) as [tex]2^{2} = 2^{x-3}[/tex] ⇒ x-3 = 2 ⇒ x = 5. It has a translation to the "right".
So, it is clear that only [tex]g(x) = 2^{x-3}[/tex] holds true and have a translation to the "right" by "c" units.
So, [tex]g(x) = 2^{x-3}[/tex] is the correct function equation that shows the corresponding transformation as shown in figure.
Keywords: transformation, function
Learn more about transformation of function from brainly.com/question/5602886
#learnwithBrainly